1995
DOI: 10.1126/science.270.5234.273
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Cobalt Oxide Magnetoresistance Materials Discovered with Combinatorial Synthesis

Abstract: The recent development of methods for generating libraries of solid-state compounds has made it possible to apply combinatorial approaches to the discovery of materials. A library of 128 members containing different compositions and stoichiometries of Ln x M y CoO δ , where Ln = Y or La and M = Pb, Ca, Sr, or Ba, was synthesized by a combination of thin-film deposition and physical masking techniques. Large magnetoresistance has been found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
232
0
7

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 541 publications
(242 citation statements)
references
References 12 publications
(1 reference statement)
1
232
0
7
Order By: Relevance
“…These methods are considered to be very efficient and quickly provide us the quantitative activity structure relationship to establish the criteria for designing novel functional materials, which have been extensively used for the discovery of functional electronic thin film materials, novel polymers, and catalysts since the mid-1990s (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These methods are considered to be very efficient and quickly provide us the quantitative activity structure relationship to establish the criteria for designing novel functional materials, which have been extensively used for the discovery of functional electronic thin film materials, novel polymers, and catalysts since the mid-1990s (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Bismuth layered perovskite ferroelectric films, SrBi 2 Ta 2 O 9 (24) and (Bi,La) 4 Ti 3 O 12 (BLT) (25), have drawn an interest for ferroelectric random-access memory because of the fatigue-free properties over 10 10 read/write cycles, unlike Pb(Zr,Ti)O 3 (PZT) (26,27 with BLT powder showed that 2P r was maximum when the Bi/La was 3.75/0.25 (33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructures should also provide the opportunity to study basic scientific phenomena that occur at small dimensions: one example is quantum confinement observed in nanostructures [1].Although microfabrication has its basis in microelectronics and most research in microfabrication has been focused on microelectronic devices [2], applications in other areas are rapidly emerging. These include systems for microanalysis [3 -6], micro-volume reactors [7,8], combinatorial synthesis [9], microelectromechanical systems (MEMS) [10, 1l], and optical comPonents [r2-r41.…”
mentioning
confidence: 99%
“…Most are fabricated from silicon using standard microlithographic techniques (silicon bulk micromachining and polysilicon surface micromachining) 144-461. With these methods, thousands of mechanical elements (for example, cantilevered beams, springs,linkages, mass elements and joints) can be batch-fabricated on a single silicon substrate [9,11]. Microactuators, micromotors and microengines [46] have been fabricated for optical switches, fluid pumps [a7], systems for drug delivery and microchemical analysis and high-speed rotational gyros for navigation [48][49][50][51].More recently, surface micromachining techniques have been used to fabricate miniaturized optical components [12][13][14].…”
mentioning
confidence: 99%